Differential Cross-section Measurements for 3He Elastic Scattering on 16O and 27Al. Issue 1 (1st October 2022) - Maragkos, F; Bosmpotinis, K; Cosic, D; Fazinić, S; Foteinou, V; Kokkoris, M; Krmpotić, M; Patronis, N; Provatas, G; Taimpiri, E; Tsakiris, Th
Abstract: In the present work measurements to determine the differential cross section values for the elastic scattering of 3 He on 16 O and 27 Al were carried out at the Ruđer Bošković Institute (RBI) Tandem Accelerator Facility in Zagreb, Croatia, covering the E3He, lab =3500-5600 keV energy range, using four Silicon Surface Barrier (SSB) detectors positioned at the backscattering angles of 130°, 145°, 157.7° and 165 ο . The target was constructed at the facility and was comprised of a thin, self-supporting aluminum foil, upon which a thin layer of nat B (isotopic ratio: 11 B 80.1%, 10 B 19.9%), along with 12 C, 14 N, 16 O, was deposited using the sputtering technique. In addition, an ultra-thin layer of 197 Au was evaporated on top for wear protection and normalization purposes.